Speech act modes in the thesis examination process: The Case of a private university - Yusrizal; Anggia Pratiwi; Sri Utaminingsih (Indonesian Research Journal in Education |IRJE|, 2025)
This research examined speech act modes in the thesis examinations of students in Indonesian Language and Literature Education at the Faculty of Teacher Training and Education, Universitas Merangin. This research used a qualitative descriptive research design. The data obtained in this research consisted of words, phrases, clauses, and sentences during the thesis examination. Data analysis was conducted using a content analysis method that focused on the quality of meaning in the context of direct and indirect speech acts. The direct and indirect speech act modes in the examination process conducted by the examiners and students were found to be as follows:1) Declarative mode, including for managing speaking turns, opening the exam, informing, ordering, and so on; 2) Interrogative mode, aimed at asking, ordering, refuting, investigating, clarifying, and so on; 3) Imperative mode, used for ordering, prohibiting, arguing, expressing gratitude, apologizing, and so on. In-depth research in pragmatic studies is necessary to inform the development of thesis course learning plans and the implementation of thesis examinations.